Solve for and in terms of and in the equations
Follow Math Help Forum on Facebook and Google+
Originally Posted by lilikoipssn Solve for and in terms of and in the equations From the second equation it follows that y = b - x. Substitute this into the first equation: 2x + 3(b - x) = a. Now expand and solve for x. Once you have x, substitute it into y = b - x and solve for y.
Hello, From the second equation, we have : x=b-y Then if we replace it in the first one, we get : 2(b-y)+3y=a 2b-2y+3y=a y=a-2b Hence x=b-(a-2b)=-a+3b
View Tag Cloud